2018
DOI: 10.1093/ndt/gfy176
|View full text |Cite
|
Sign up to set email alerts
|

APOL1 risk genotype in European steroid-resistant nephrotic syndrome and/or focal segmental glomerulosclerosis patients of different African ancestries

Abstract: The HR genotype is frequent in FSGS patients with African ancestry in our cohort, especially in those originating from the West Indies, and confer a poor renal prognosis. It is usually not associated with other causative mutations in monogenic SRNS genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…As expected (Eddy & Symons, 2003), the children with SRNS were significantly older at presentation, otherwise the groups were demographically similar. Genetics are known to play a role in steroid-responsiveness (Adeyemo et al, 2018;Asharam et al, 2018;Govender et al, 2019;Gribouval et al, 2018Gribouval et al, , 2019. However, while genetic and other mechanisms underlying steroid-responsiveness in this small cohort were not evaluated in the present study, they have been the subject of previously reported biomarker studies (Agrawal et al, 2020;Gooding et al, 2020).…”
Section: Hypercoagulopathy Improves In Children With Steroid-sensitmentioning
confidence: 83%
“…As expected (Eddy & Symons, 2003), the children with SRNS were significantly older at presentation, otherwise the groups were demographically similar. Genetics are known to play a role in steroid-responsiveness (Adeyemo et al, 2018;Asharam et al, 2018;Govender et al, 2019;Gribouval et al, 2018Gribouval et al, , 2019. However, while genetic and other mechanisms underlying steroid-responsiveness in this small cohort were not evaluated in the present study, they have been the subject of previously reported biomarker studies (Agrawal et al, 2020;Gooding et al, 2020).…”
Section: Hypercoagulopathy Improves In Children With Steroid-sensitmentioning
confidence: 83%
“…In 2010, 2 mutually exclusive polymorphisms (G1 and G2) in the apolipoprotein L1 (APOL1) gene, commonly found in people of African ancestry, were identified to increase the risk of chronic kidney disease (CKD) in homozygous or compound heterozygote individuals by 7-to 30-fold, accounting for the higher prevalence of kidney failure in African Americans (1)(2)(3)(4). These mutations originated in ancestral populations in West Africa and are now being described as associated with CKD risk in other descendant populations, highlighting West African ancestry as the ethnically linked population (5). The APOL1 risk alleles have been shown to strongly associate with various forms of nondiabetic nephropathy previously thought to be unrelated, including focal segmental glomerulosclerosis (FSGS), HIV-associated nephropathy (HIVAN), hypertensive-attributed kidney disease, lupus nephritis, and IFN therapy-related collapsing glomerulopathy (1,3,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…APOL1 , apolipoprotein L1, encodes a secreted high-density lipoprotein, which binds to apolipoprotein A-I. Some researches indicated APOL1 is related to cardiovascular disease and renal disease [ 41 , 42 ]. H1–2 , H1.2 linker histone, is also called HIST1H1C .…”
Section: Discussionmentioning
confidence: 99%